THE RELATIONSHIP BETWEEN IMMIGRATION, ACCULTURATION AND PSYCHOLOGICAL WELL-BEING THE CASE OF TURKISH YOUTH IN AUSTRIA - Levent KIYLIOGLU; Heinz WIMMER (Nesne Psikoloji Dergisi, 2015)
Psychological research in culturally plural societies has traditionally been divided into two domains: acculturation and ethnic relations. Berry’s model of acculturation and psychological well-being is highly regarded and widely recognized as in the field. His two-dimensional model of acculturation is based upon the multicultural ideology where individuals and groups are given the opportunity to choose among various elements of ethnic and host cultures to form their own unique blends of identity and culture. The findings support the Berry’s proposal that acculturation is two-dimensional (ethnic/cultural and host society identification) for acculturating immigrants. But the process of acculturation is different depending on the life domains being considered. Youngsters do not endorse both cultures to the same degree in all domains, which means acculturation preferences for Turkish youngsters between the ages of 12-15 are domain dependent. In terms of average point acculturation preferences, Turkish youth endorsed integration more than any other acculturation strategies. Significant correlation was found among self-esteem and separation acculturation attitude for reading books domain. Second significant correlation was found among self-esteem and margina¬lization acculturation attitude for work domain.